Neutrophil Myo5c gene downregulation is associated with postoperative organ dysfunction following pediatric cardiac surgery with cardiopulmonary bypass - Maisat, Wiriya; Sandhu, Sumiti; Kim, Samuel; Van Pelt, Hanna; Kong, Sek Won; Ibla, Juan; Yuki, Koichi (Frontiers in Cardiovascular Medicine, 2025)
IntroductionPediatric cardiac surgery with cardiopulmonary bypass (CPB) carries substantial risks of postoperative organ dysfunction and mortality, making the identification of biomarkers for postoperative organ dysfunction crucial for enhancing patient outcomes. As neutrophils play a major role in the perioperative setting and act as double-edge swords to the host, we examined neutrophil transcriptomic profiles in pediatric patients undergoing cardiac surgery with CPB.MethodsWe enrolled into this study from May 31, 2022, to February 22, 2023.Results32% developed postoperative complications, mainly in the respiratory and cardiovascular systems. Patients in the complication group showed higher PELOD-2 scores on postoperative day 2. These patients experienced longer duration of mechanical ventilation and extended ICU and hospital stays. RNA sequencing of neutrophils revealed significant changes in gene expression after CPB, with the myo5c gene emerging as a key downregulated transcript. Its expression was inversely correlated with PELOD-2 score, IL-6 levels, and markers of neutrophil and platelet activation. Furthermore, myo5c-knockout HL60 cells exhibited enhanced neutrophil extracellular traps (NETs) formation upon stimulation, supporting a potential regulatory role for myo5c in neutrophil activation and systemic inflammation.DiscussionWhile myo5c was not an independent predictor of complications, its expression was consistently associated with clinical severity, suggesting it may serve as a useful biomarker for early risk stratification of postoperative complications in this vulnerable pediatric population.